Developing WIND Media to Facilitate Students in Writing Short Descriptive Text (RETAIN, 2018)
AbstractWriting is one of complex skills should be master by students. The problems face by students could make them difficult to master it. However, students assume that writing is difficult, boring, and exhausting activity. This condition will make ineffective learning. Other problem is the students are difficult to generate and to develop the ideas which make them feel difficult to start their writing project. Thus, the teacher needs a new way to ease the students learning. Suitable media which can help students to write easily should be made. The purpose of this study is to develop media named “Wheel Instruction and Cards” or “WIND” media. This media aims to facilitate students in writing descriptive text. This study is using modified R&D model from Dick and Carey. This study will explain the process of developing media and also include the students’ responses toward the implementation of the media.Keywords: writing, media, WIND, descriptive textAbstrakMenulis adalah salah satu keterampilan yang sulit yang harus dikuasai siswa. Siswa beranggapan bahwa menulis adalah aktivitas yang sulit, membosankan dan melelahkan. Kondisi ini dapat membuat pembelajaran tidak efektif. Permasalahan lain yang dihadapi siswa adalah mereka kesulitan untuk menghasilkan dan mengembangkan ide yang akan membuat mereka mereasa kesulitan untuk memulai aktivitas menulis. Maka dari itu, guru membutuhkan cara baru untuk mempermudah siswa dalam belajar. Salah satu cara adalah dengan menggunakan media yang sesuai dengan level siswa. Tujuan dari penelitian ini adalah untuk mengembangkan media bernama “Wheel Instruction and Cards” atau “WIND”. Tujuan dari pembuatan media ini adalah untuk mefasilitasi siswa dalam menulis teks deskriptif. Penelitian ini menggunakan model penelitian dan pengembangan yang dimodifikasi berdasarkan teori Dick dan Carey. Penelitian ini akan menjelaskan proses pengembangan media dan termasuk juga respon siswa terkait penerapan media.Kata Kunci: menulis, media, WIND, teks deskriptif